PENDAMPINGAN OPTIMALISASI DIGITAL MARKETING UNTUK MENINGKATKAN BRAND AWARENESS DESA WISATA WANUREJO BOROBUDUR - Rizqa Ula Fahadha; Sutarto Sutarto (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service activity was carried out with the aim of optimizing the implementation of digital marketing to increase the brand awareness of Wanurejo Tourism Village as a highly competitive, community-based tourism destination. The main issues identified were the low level of brand awareness, inconsistent digital image, and content quality that has not yet been able to optimally represent the uniqueness and potential of the village. This activity was conducted through a phased content marketing approach over three years, with stages of optimization, evaluation, and strategy consolidation. The methods used included technical training, narrative content production, participatory observation, and data-based evaluation using social media analytics. The results showed that an adaptive, data-driven digital marketing strategy focused on relevant and engaging content can increase audience reach, improve the village’s digital image perception, and strengthen community participation in tourism promotion. The conclusion of this activity highlights the importance of integrating structured content strategies with the strengthening of local capacity to support the sustainable, independent promotion of the tourism village.